Hematopoietic elements: The foreign invaders of the adrenal gland - Case series and review of literature - L.A. Nigam; A.V. Vanikar; R.D. Patel; K.V. Kanodia; K.S. Suthar (Elsevier, 2020)
Hematopoietic elements identified outside of the bone marrow are defined as extramedullary hematopoiesis (EMH) and is observed normally during embryonic development and fetal life. Conditions secondary to insufficient bone marrow function or ineffective hematopoiesis, malignancies, as well as stromal disorders of the bone maylead to EMH in adult liver, spleen and lymph nodes. EMH in the adrenal is rare, with very few cases reported. We present a case series of five patients, of which two presented with non-specific complaints and three were found to have an incidental abdominal mass on radiology. These were reported as EMH of adrenal gland on histology. None of our five cases had any underlying disease making the present case series interesting and unique.